Genomic instability in long-term culture of human adipose-derived mesenchymal stromal cells - Malagutti-Ferreira, M. J. [UNESP]; Crispim, B. A.; Barufatti, A.; Cardoso, S. S.; Guarnier, L. P.; Rodríguez, F. F. [UNESP]; Soares, M. R.; Antunes, R. N.S.; Ribeiro-Paes, J. T. [UNESP] (FapUNIFESP (SciELO), 2023)
Mesenchymal stromal/stem cells stem (MSC) have been widely studied due to their great potential for application in tissue engineering and regenerative and translational medicine. In MSC-based therapy for human diseases, cell proliferation is required to obtain a large and adequate number of cells to ensure therapeutic efficacy. During in vitro culture, cells are under an artificial environment and manipulative stress that can affect genetic stability. Several regulatory agencies have established guidelines to ensure greater safety in cell-based regenerative and translational medicine, but there is no specific definition about the maximum number of passages that ensure the lowest possible risk in MSC-based regenerative medicine. In this context, the aim of this study was to analyze DNA damage and chromosome alterations in adipose-derived mesenchymal stromal cells (ADMSC) until the eleventh passage and to provide additional subsidies to regulatory agencies related to number of passages in these cells. Thus, two methods in genetic toxicology were adopted: comet assay and micronucleus test. The comet assay results showed an increase in DNA damage from the fifth passage onwards. The micronucleus test showed a statistically significant increase of micronucleus from the seventh passage onwards, indicating a possible mutagenic effect associated with the increase in the number of passages. Based on these results, it is important to emphasize the need to assess genetic toxicology and inclusion of new guidelines by regulatory agencies to guarantee the safety of MSC-based therapies for human diseases.
Keywords: Cell culture; Cell therapy; Comet assay; Genetic toxicology; Micronucleus test; Stem cells